2017
DOI: 10.1038/mp.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

The familial co-aggregation of ASD and ADHD: a register-based cohort study

Abstract: Autism spectrum disorders (ASD) and attention-deficit/hyperactivity disorder (ADHD) frequently co-occur. The presence of a genetic link between ASD and ADHD symptoms is supported by twin studies, but the genetic overlap between clinically ascertained ASD and ADHD remains largely unclear. We therefore investigated how ASD and ADHD co-aggregate in individuals and in families to test for the presence of a shared genetic liability and examined potential differences between low- and high-functioning ASD in the link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
145
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(165 citation statements)
references
References 43 publications
11
145
2
4
Order By: Relevance
“…Conversely, the excess cross-aggregation in siblings indicates shared etiologic (familial) factors. This finding is consistent with numerous studies using genetically informed methods that have suggested shared genetic influences on both ASD and ADHD traits and diagnoses, 5,6,9 and several that have highlighted shared copy number variants, 10,25 although other studies have not identified genetic overlap. 8,26 …”
Section: Discussionsupporting
confidence: 91%
“…Conversely, the excess cross-aggregation in siblings indicates shared etiologic (familial) factors. This finding is consistent with numerous studies using genetically informed methods that have suggested shared genetic influences on both ASD and ADHD traits and diagnoses, 5,6,9 and several that have highlighted shared copy number variants, 10,25 although other studies have not identified genetic overlap. 8,26 …”
Section: Discussionsupporting
confidence: 91%
“…A register-based study in Sweden found that individuals with ASD and their relatives were at increased risk of ADHD. The pattern of association across relatives supported the existence of a genetic overlap between clinically ascertained ASD and ADHD [50]. Some features of ASD are differentially linked to either the inattentive or the hyperactive-impulsive components of ADHD [51,52].…”
Section: Psychiatric Comorbiditymentioning
confidence: 72%
“…However, sex differences regarding these disease phenotypes are gaining attention, as fewer girls have been reported to have ASD. Notably, the possibility of missed diagnoses or misdiagnoses among girls is mentioned DSM‐5 . Finally, the sample of the present study was small; hence, it was impossible to evaluate the relationship between ASD and ADHD symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…However, considering the frequency of this comorbid presentation, the current literature on the comorbidity of ASD with ADHD remains insufficient. Approximately 50%–80% of individuals with ASD develop ADHD, and persons with ASD and their relatives are at higher risk of having ADHD . The pattern of association across different familial relationships supports a genetic overlap between clinically ascertained ASD and ADHD .…”
mentioning
confidence: 76%
See 1 more Smart Citation